Job-related risk taking behaviors, work attitude and work values of security guards in UPV Miag-ao, Iloilo. - Leonida, Mary Hope L. (2005.)
This study sought to find out the job-related risk taking behavior, work attitude, and work values of security guards in UPV, Miagao. Thirty-seven (37) regular security guards employed under the Galila Security Agency Inc. as of the SY 2004-2005 were purposely chosen to serve as respondents., Three instruments were utilized for this study namely: risk-taking questionnaire, work attitude scale, and work values assessment scale . Results showed that UPV security guards are low risk takers and are always careful in taking risks pertaining to their job. They have also positive attitude towards their job indicating that they are satisfied, involved, and committed to the organization and their job. Intrinsically, they put high value on precision work, knowledge, and influence people. However, they are extrinsically motivated with financial gain in their job.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Security Guards -- UPV Miagao, Iloilo